Phytoremediatioan of monoazo and diazo dyes in wastewater using up-flow constructed wetland - Chen Siaw Fun (School of Environmental Engineering University Malaysia Perlis, 2011)
Application of a sequential anaerobic and aerobic in a constructed wetland system can enhance the treatment performance of textile wastewater to efficiently remove color, organic compounds, and intermediate aromatic amines. Four laboratory-scale up-flow constructed wetland (UFCW) reactors planted with Phragmites australis were constructed to investigate the treatment performance between aerated and non-aerated reactors to treat methyl orange (MO) and reactive black 5 (RB5) containing synthetic wastewater. The treatment performances of UFCW reactors were greatly improved for two days hydraulic retention time (HRT) compared to 1 day HRT. The non-aerated reactors which demonstrated an almost entire anaerobic environment as evidenced by oxidation reduction potential (ORP) profile yielded a better dyes removal efficiency with 93.12% (MO) and 89.49% (RB5) compared to the aerated reactor with only 75.48% (MO) and 81.29% (RB5) when the influents dyes concentration was 50 mg/L. Decolorization efficiency of monoazo dye MO was higher than diazo dye RB5. On the other hand, supplementary aeractors proved that higher reduction on COD 85% .